The bismuth orthotantalate with high anisotropic thermal expansion. (December 2019) - Zhuk, N.A.; Krzhizhanovskaya, M.G.; Belyy, V.A.; Sekushin, N.A.; Chichineva, A.I.
Abstract: The triclinic phase of the bismuth orthotantalate (β-BiTaO4 ) exhibited strong anisotropy of thermal expansion in the temperature range of 25–750 °C. The character of the thermal expansion of β-BiTaO4 changed radically near 200 °C, which was not observed in its isomorphic analog (β-BiNbO4 ). In the same temperature range the electrical properties also exhibited the local extremum. Crystal structure of β-BiNbO4 was refined at 25, 200, 400 and 600 °C from powder X-ray diffraction data. The role of bismuth lone-electron pair is discussed. β-BiTaO4 has a potential to be used as a thermal expansion material. Graphical abstract: Unlabelled Image